The growth of tourism and its impact on the protected areas of Iceland - Dysková, S.; Petrikovičová, L.; Roubalová, M. (Zenodo, 2021)
: Iceland or the land of fire and ice has been a great attraction for many tourists in recent years. Every year thousands of tourists visit the country with more than 360,000 inhabitants. Interest in the country began to grow approximately ten years ago, In April 2010, when Eyjafjallajökull, a volcano in southern Iceland, began spewing several kilometres of volcanic ash into the atmosphere. The cloud of ash forced the greatest airspace closure since World War II, cancelling nearly 100,000 flights and disrupting the travel plans of tourists and business travelers alike throughout northern Europe. The island had traditionally held little appeal to international tourists and most of the country’s GDP came from its fishing industry. Then, in 2008, the financial crisis sent the world’s economy into a tailspin which triggered a series of hardships that threatened to destroy the country’s reputation. The Icelandic Krona depreciated significantly as Icelandic banks were unable to repay their short-term debt, and over the course of a few weeks Iceland garnered more media attention than it had had in the previous two decade. Although the number of tourists in 2019 was lower than in the previous year, there are still so many. In addition to increasing economic growth, this trend of increasing tourism has a negative impact on the environment in the country. In this paper we focused on the most visited protected areas and their perception by tourists from an environmental point of view. We evaluate the impact of tourism and its impact on the landscape. Part of the work is a questionnaire survey focused on tourists, their national composition, length of stay in the country and regions that they traveled during their visit and so on